PENGARUH MANAJEMEN KEPALA SEKOLAH DAN PROFESIONALISME GURU TERHADAP KINERJA GURU - Puspitasari, Yeni; Tobari, Tobari; Kesumawati, Nila (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2021)
This study determined the effect of headmaster management and teacher professionalism on teacher’s performance. This research used quantitative methods with correlational type of research. The population of this study were 309 teachers Tanjung Raja Public Elementary School. The research sample was 76 people. Data collection techniques using documents and questionnaires. Data were analyzed using correlation analysis and multiple regression techniques. The results of the study show that (1) school principal management influences the performance of teachers; (2) teacher professionalism does not affect the performance of teachers; (3) school management and teacher professionalism do not affect the performance of teachers.